Discusses the message in Poetry for the Indonesian People of poems Korean poets: Analisis Amanat dalam Puisi Buat Rakyat Indonesia Penyair Korea - Erik Mayzaldi; Abdul Malik; Ahada Wahyusari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research discusses the message in Poetry for the Indonesian People, a of poems from Korean poets. The aim of this research is to convey the message in Poetry for the Indonesian People, a collection of poems from Korean poets. The method used in this research is descriptive qualitative. The data in this research are words or sentences contained in Poetry for the Indonesian People, a collection of poems from Korean poets. The data collection techniques used to obtain research data are documentation, reading, listening and note-taking techniques. The data analysis technique used is a content analysis technique by reading, analyzing, describing and concluding the contents of the message in Poetry for the Indonesian People, a collection of poems from Korean poets. The results of this research are that there is a message in Poetry for the Indonesian People, a collection of poems from Korean poets, in the implicit and explicit form of the 3 poems that were analyzed.